AB0863 The popliteus groove in the lateral femoral condyle: a shelter for monosodium urate crystals?. (15th June 2017) - Matteo, A Di; Cipolletta, E; Ausili, M; Filippucci, E; Grassi, W
Abstract : Background: Gout is a crystal related arthropathy characterized by deposition of monosodium urate (MSU) crystals at articular and periarticular structures. Ultrasound (US) has gained an important role in the diagnosis of gout due to its capability to clearly detect various expressions of MSU crystal depositions in joints, tendons and bursae [1]. The popliteus tendon inserts in a depression on the outer side of the lateral femoral condyle. It has a close connection to the lateral meniscus and is surrounded by the popliteal recess which is in direct communication with the knee joint cavity [2]. Objectives: To evaluate the prevalence of US findings indicative of MSU crystal deposition at the popliteus groove in patients with gout. Methods: Consecutive patients with gout, diagnosed according to the 2015 ACR/EULAR criteria, and disease controls diagnosed according to the corresponding diagnostic/classification criteria were enrolled. All the patients underwent a bilateral US examination (carried out using a Logiq 9 US system working with a linear probe operating at 15 MHz) at the popliteus groove level. The US examination was performed with the patient lying supine on the examination bed. A knee flexion of approximately 45° was necessary to visualize the popliteus groove in the lateral aspect of the femoral condyle just deep to the proximal part of the lateral collateral ligament. The following US abnormalities indicative of MSU crystal depositions were evaluated: isolated shining dots, aggregates (heterogeneous hyperechoic foci that maintain their persistent high degree of reflectivity which occasionally may generate posterior acoustic shadow) and tophi (inhomogeneous hyperechoic/hypoechic material surrounded by a small anechoic rim which may generate posterior acoustic shadows). Results: We enrolled 17 patients with gout and 22 disease controls: 9 calcium pyrophosphate deposition disease (CPPD), 8 rheumatoid arthritis and 5 psoriatic arthritis. A total 78 popliteus groove were examined by US. US findings indicative of MSU crystal deposition were detected in at least one knee in 13 out of 17 gout patients (76.5%) and in 7 out of 22 controls (31.8%). Table 1 shows the prevalence of the US abnormalities indicative of MSU crystal deposition in the two groups. Six out of the 10 US abnormalities (60%) found in controls were detected in CPPD patients. Conclusions: These preliminary results suggest that the popliteus groove could be regarded as a sentinel area for detecting MSU crystals. These findings should lead to further investigations aimed at identifying the factors and associated with MSU crystals deposition at popliteus groove level. References: Neogi T, Jansen TLTA, Dalbeth N, et al. 2015 Gout Classification Criteria: An American College of Rheumatology/European League Against Rheumatism Collaborative Initiative. Arthritis Rheumatol 2015;67:2557–68. Jadhav SP, More SR, Riascos RF, et al. Comprehensive review of the anatomy, function, and imaging of the popliteus and associated pathologic conditions. Radiographics. 2014 Mar-Apr;34(2):496–513. Disclosure of Interest: None declared